Inflation in North America: A Critical Review and Analysis of the Year 2022 - Mbah, Ruth Endam; Hultquist, Laura; Repp, Rande (Advances in Social Sciences Research Journal, 2023)
The year 2022 has been a year of unprecedented change and global unrest. The world is still struggling to recover from the first global pandemic in over a century and the coordinated global response thereof which changed both the social and the economic landscapes. Amid this recovery, the world economy has been hit by the Russia-Ukraine war, the effect of climate change on agriculture, citizen unrest and leadership changes in nations across the globe, global supply-chain disruptions, and record-high inflation. This review presents a comparative analysis of the causes/impacts of inflation during 2022 in North America as well as discusses mitigation strategies proposed by the nations therein. Monetarism is used to review North America’s responses to the high inflation rates. Findings indicate that the causes for inflation in North America were very similar for all three countries. These causes included disruption in the supply chain, an excessive rise in demand over supply, the impact of the Russian-Ukraine war, the lingering effects of the governmental response to Covid-19, a tight labor market, expansionary monetary policies by the central banks, and the global impact of drought on agriculture. Our findings also show that the impact of this record-high inflation aligned across all three countries like elevated food prices, housing/rental costs, energy costs, gas prices, household operational costs, healthcare insurance, education cost, and increased poverty, especially among low and fixed-income earners. The central banks of all three countries are using monetary policies to mitigate the situation by increasing their interest rates. However, monetary policies on their own cannot solve the situation and must be complemented by fiscal policies. This can be evidenced by the intervention of all three governments in the high-inflation challenge. Nevertheless, this review is limited to North America, thus, it will be essential for future research to focus on other countries and regional blogs.